Analysis of Financial Distress of Cigarette Sub Sector Companies Listed on the Indonesia Stock Exchange Period 2017-2021 - Muhammad Imaduddin As'ad; Agung Widhi Kurniawan; Anwar; Anwar Ramli; Andi Mustika Amin (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine the potential for bankruptcy experienced by industrial companies in the cigarette sub-sector in 2017-2021. This type of research uses descriptive quantitative with a population of issuers in the cigarette sub-sector during 2017-2021. Sampling using purposive sampling method to get 4 companies. Data collection was carried out using documentation techniques. Data analysis techniques using the First Altman Z-Score. The results showed that in the last five years the potential for bankruptcy in cigarette sub-sector companies was low because there was only one company that had the potential to go bankrupt, namely PT. Bentoel Internasional Investama Tbk. The company is in a vulnerable precautionary zone for bankruptcy during 2018-2019 and there are indications that the company is experiencing financial difficulties in 2020. The company PT. Gudang Garam Tbk, PT. Hanjaya Mandala Sampoerna, PT. Wismilak Inti Makmur Tbk, has no potential for bankruptcy.